Perspektif Mahasiswa Prodi Teologi IAKN Tarutung tentang Pacaran yang Sehat - Sarnita Sari Tumangger; Erman S Saragih; Hanna Dewi Aritonang; Haposan Silalahi; Bestian Simangunsong (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
The purpose of this study was to determine the perspectives of theology study program students on healthy dating based on Christian ethics. The method used in this study is a descriptive qualitative method. Data were collected through observation and interviews with eight theology study program students from 2020-2021. The results of the study showed that students have three main views related to the foundations of healthy dating, namely: Good communication, mutual respect, and maintaining bodily purity. Based on interviews with eight students, it was found that these three perspectives are very important in building harmonious relationships and in accordance with dating ethics. However, students face challenges in maintaining healthy relationships, including environmental influences, temptations of lust, and unclear goals in relationships. For this reason, the application of boundaries and education regarding healthy dating is very necessary to help students understand and live relationships that are in accordance with Christian values. This study is expected to contribute to instilling ethical dating values ​​among theology students.